Observational Constraints on Model with Specific Deceleration Parameter - Beesham, Aroonkumar (Contemporary Mathematics, 2025)
We place observational constraints on a cosmological model with a specific deceleration parameter that depends on the scale factor that has been discussed recently. This form of the deceleration parameter has been discussed by authors in several papers, but none of them have applied observations to constrain the variables of the model. We carry this out with the cosmic chronometer, supernovae and the baryon acoustic oscillation datasets. Use is made of Markov Chain Monte Carlo analysis which implements Bayesian methods in cosmology. This is used to obtain the optimum values for the relevant parameters, which are then used to plot the kinematical and physical parameters of the model. We discuss the verious cosmographic parameters of the model, such as the deceleration and state-finder parameters. There are several issues with any cosmological model based on this deceleration parameter concerning the values of some of the parameters. The transition redshift of the model and the current value of the deceleration parameter do not match with the Planck data. Thus the model does not seem viable.